Is household food insecurity associated with overweight/obesity in women? - Fatemeh Mohammadi; Nasrin Omidvar; Gail G Harrison; Mahmood Ghazi-Tabatabaei; Morteza Abdollahi; Anahita Houshiar-Rad; Yadollah Mehrabi; Ahmad Reza Dorosty (Tehran University of Medical Sciences, 2013)
Despite reports on association between overweight/obesity among women and household food insecurity (FI) in developed countries, such association is not evident in developing countries. This study aimed to assess the association between household FI and weight status in adult females in Tehran, Iran.In this cross-sectional study, 418 households were selected through systematic cluster sampling from 6 districts of Tehran. Height and weight were measured and body mass index (BMI) was calculated. Socio-economic status of the household was assessed by a questionnaire. Three consecutive 24-hour diet recalls were completed. FI was measured using adapted Household Food Insecurity Access Scale. Logistic regression was used to test the effects of SES and food security on weight status, simultaneously. Using Structural Equation Modeling (SEM) potential causal relationships between FI and weight status was explored.Only 1.0% of women were underweight, while 40.3% were overweight and 33% were obese, respectively. Severe, moderate, and mild food insecurity was observed in 11.5, 14.7, and 17.8%, respectively. Among women in moderately food insecure households, the possibility of overweight was lower than those of food secure households (OR 0.41; CI95%:0.17-0.99), while in severely food insecure households, the risk of abdominal obesity for women was 2.82 times higher than food secures (CI95%:1.12-7.08) (P